If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -5x = 8 + x Solving 3 + -5x = 8 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3 + -5x + -1x = 8 + x + -1x Combine like terms: -5x + -1x = -6x 3 + -6x = 8 + x + -1x Combine like terms: x + -1x = 0 3 + -6x = 8 + 0 3 + -6x = 8 Add '-3' to each side of the equation. 3 + -3 + -6x = 8 + -3 Combine like terms: 3 + -3 = 0 0 + -6x = 8 + -3 -6x = 8 + -3 Combine like terms: 8 + -3 = 5 -6x = 5 Divide each side by '-6'. x = -0.8333333333 Simplifying x = -0.8333333333
| 2-5t+8+5t-8= | | 13x-5=4(3x+3)-7 | | 6(n-1)=4n+8 | | 3t-3=2t+6 | | 3x+1=x-13 | | x-6=33 | | 6/11-3/11 | | 1=-2/3(x-6) | | X/x-4+8=4/x-4 | | 4(3x-3)-3(2x-4)=0 | | 1=-2/3(x-1/6) | | X+3(5+3x)=95 | | 64x^2-112x=0 | | 3/8+5/12 | | (4x+5)(x^2+2x-8)=0 | | .24(57.5)+.17y=17.8 | | 3x+6.84=2x | | -7+-24= | | 3/10-1/4 | | 29-(x+6)=9x-7 | | 3r+8=20 | | 4*(x+2)=18 | | -17=p+3-3p | | 9y-12-4y+9=0 | | 12+9x-6x-19= | | c(c-5)=14 | | 8y-14-4y+9=0 | | 5.3=z-2.7 | | 4x=x-25 | | 6(w+1)=2(w+5) | | 4-3x-10=-18 | | -6(1-5x)+x=2x-35 |